KEANEKARAGAMAN HAYATI ZOOPLANKTON DI PULAU PELAPIS, KABUPATEN KAYONG UTARA - Dahlia Wulan Sari; Achis Martua Siregar (JURNAL BORNEO AKCAYA, 2022)
Zooplankton is an animal plankton that connects producers and secondary consumers in an aquatic ecosystem. Data related to the condition of the waters of Pelapis Island as one of the mariculture zone in West Kalimantan is currently still limited. The zooplankton community structure is one of the important things in the development of mariculture. Therefore, this study aims to present data related to the zooplankton community structure in Pelapis Island Waters as the basis for developing mariculture. Sampling was carried out using a plankton net and preserved using Lugol. Identification was carried out at the Nahdlatul Ulama University Laboratory, West Kalimantan. The analysis was conducted to determine the index of diversity, evenness, and dominance of zooplankton. The results showed that the abundance of zooplankton in the waters of Pelapis Island dominated by the sub-phylum Crustacea and fish eggs at 44.05±1.09% and 35.07±2.97%, respectively. The number of genera found in this study was nine genera, and 4 of them were crustaceans. Zooplankton diversity showed moderate to low values and high dominance at Station 8.